2002
DOI: 10.3171/jns.2002.97.supplement_5.0415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma knife radiosurgery of pituitary adenomas on pituitary function

Abstract: Object. The authors undertook a retrospective analysis of the incidence and time course of pituitary insufficiency following gamma knife radiosurgery (GKS) for pituitary adenomas. Methods. Pituitary adenomas in 92 patients were analyzed. There were 61 hormonally inactive tumors, 18 prolactinomas, and nine somatotropic and four adrenocorticotropic adenomas. The mean tumor volume was 3.8 cm3 (range 0.2–14.6 cm3). The mean prescription dose was 15 Gy. The mean prescription isodose was 50.7%. The mean follow-up ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(69 citation statements)
references
References 30 publications
5
62
1
1
Order By: Relevance
“…This is reasonably consistent with the results of three GKRS series [15,23,47]. Vladyka et al [47] found a mean dose of more than 17 Gy and 20 Gy to be a risk factor for impairment of the gonadotrophic and corticotrophic/thyrotrophic function, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…This is reasonably consistent with the results of three GKRS series [15,23,47]. Vladyka et al [47] found a mean dose of more than 17 Gy and 20 Gy to be a risk factor for impairment of the gonadotrophic and corticotrophic/thyrotrophic function, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, local control of tumor growth is similar between fractionated and single fraction radiation therapy with rates of approximately 95% at 5 years, similar to nonfunctioning adenomas [4,19]. In contrast, stereotactic radiosurgery appears to produce a faster hormonal ablative response than fractionated radiation [3,8,20].…”
Section: Single Versus Fractionated Radiation Therapymentioning
confidence: 78%
“…Linac-based stereotactic radiotherapy and radiosurgery as well as gamma knife radiosurgery have emerged as treatment options, and the results achieved by those techniques are encouraging [7,11,24,27,28,35,36]. Whether late side effects (e.g., hypopituitarism) following stereotactic techniques are less frequent than after conventional external-beam radiotherapy has not yet been shown, since most follow-up data are still limited [5,8,14,18,20,23,29].…”
Section: Discussionmentioning
confidence: 99%